Knowledge about the relation between child growth and formula prepartion at home among mothers - Braikan, Ahmed Al; Marjan, Amjaad Al; Qurashi, Mansour Al (International Journal of Contemporary Pediatrics, 2017)
Background: Human breast milk is considered to be the best source of infant nutrition. Extensive evidence has shown mother’s milk contains a variety of bioactive agents that modify the function of the gastrointestinal tract and the immune system, as well as in brain development. Objective of the study was to evaluate the level of knowledge about the child growth and formula preparation, to assess the knowledge of the relation between failure of preparation peoper formula and child growth complication. Methods: This will be a community base cross section study collected from an online survey tool. The survey was distributed electronically through the SurveyMonkey.com website to all mothers age between (18 to 40) from June 1st, 2016 to July 1st, 2016. The criteria of the survey, to be collected from Mothers age between (18 to 40). Results: In the study of knowledge about the child growth and formula preparation among mothers, we found only 20% of our targeted group learned the way of preparation from the pediatrician which indicates the requirements of more efforts from the side of health care physician. 50% of those who answered: “yes, we applied certain changes over the formula “the reason behind what they did was to help their children to gain more weight. In regard of over concentration of milk we asked about the way of preparation. The highest result was definitely wrong with answer: “I press over the scoop more than once, then adding it to the water 39.19%. Conclusions: On the other hand we found a great acknowledgment when we asked about child’s positioning during feeding. The majority said: “my child is always lying on his back, with my hand supporting his head” with percentage close to 82.22%.